How do contextual factors influence quality and safety work in the Norwegian home care and nursing home settings? A qualitative study about managers’ experiences - Ree, Eline (BMJ Open, 2019)
OBJECTIVE: Although many contextual factors can facilitate or impede primary care managers’ work with quality and safety, research on how these factors influences the managers’ continuous improvement efforts is scarce. This study explored how primary care managers experience the impact of a variety of contextual factors on their daily quality and safety work. DESIGN: The study has a qualitative design. Nine semistructured qualitative interviews were conducted at the participants’ workplaces. Systematic text condensation was used for analysis. SETTING: Five nursing homes and three home care services in Norway. PARTICIPANTS: Female primary care managers at different levels, working in different units and municipalities varying in size and location. RESULTS: The participants cited the lack of time and money as a significant impediment to quality and safety, and these resources had to be carefully allocated. They emphasised the importance of networks and competence for their quality and safety work. Delegation of responsibility among employees helped create engagement, improved competence and ensured that new knowledge reached all employees. External guidelines and demands helped them to systematise their work and explain the necessity of quality and safety work to their employees, if they were compliant with daily clinical practice in the organisation. CONCLUSIONS: Numerous contextual factors influence the managers by determining the leeway that they have in quality and safety work, by setting the budgetary constraints and defining available competence, networks and regulation. At first glance, these factors appear fixed, but our findings underscore the importance of primary care managers acting on and negotiating the environment in which they conduct their daily quality and safety work. More research is needed to understand how these managers strategise to overcome the impediments to quality and safety.